1968
DOI: 10.1677/joe.0.0420005
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Method for Estimating Oestrogens in Urine Using a Semi-Automatic Extractor

Abstract: A semi-automatic extractor was developed which processes 12 urines at a time to a stage where 'total' oestrogens can be measured by colorimetry using the Kober reaction (late pregnancy urines) or by fluorimetry using the Kober\p=m-\Ittrich procedure (non-pregnancy and early pregnancy urines). One worker can complete 12 analyses in 3\ m=1/ 2\ hr. or 24\p=n-\36 in a working day. The results obtained at oestrogen levels above 1 mg./24-hr. urine were the same as those obtained by a method specific for oestriol. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
0
1

Year Published

1970
1970
1978
1978

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(77 citation statements)
references
References 16 publications
2
74
0
1
Order By: Relevance
“…Previous work (Genazzani et at., 1975) has shown that plasma cortisol and ACfH undergo cyclic changes during the menstrual cycle. In the present study the excretion, in urine, of free corticosteroids and total oestrogens was examined as indices of adrenal and ovarian activity, respectively, The oestrogen/creatinine ratio measurements showed the normal biphasic pattern associated with follicular growth and ovulation shown by previous studies of 24-hour excretion (Brown et al, 1968). The urinary free ll-hydroxycorticosteroid/ creatinine ratio showed random fluctuations through the follicular phase.…”
Section: Methodsmentioning
confidence: 50%
“…Previous work (Genazzani et at., 1975) has shown that plasma cortisol and ACfH undergo cyclic changes during the menstrual cycle. In the present study the excretion, in urine, of free corticosteroids and total oestrogens was examined as indices of adrenal and ovarian activity, respectively, The oestrogen/creatinine ratio measurements showed the normal biphasic pattern associated with follicular growth and ovulation shown by previous studies of 24-hour excretion (Brown et al, 1968). The urinary free ll-hydroxycorticosteroid/ creatinine ratio showed random fluctuations through the follicular phase.…”
Section: Methodsmentioning
confidence: 50%
“…Twin pregnancies and those with doubtful duration were excluded. In the third trimester of pregnancy the following determinations were made: An average of 4 determinations of the biparietal head diameter using the B-scan method (Vidoson), 10 determinations of estriol and 3 of pregnandiol in urine [13,50] and 6 HPL determinations in the semm [49], 7 determinations of heat stable alkaline phosphatase (HSAP) [9], all per individual case. Biparietal head diameter values were transferred to a Standard curve that was in agreement with the one reported by HOLLÄNDER [42].…”
Section: Methodsmentioning
confidence: 99%
“…The procedure of Oakey et al, method B (1967) was carried out, as described by the authors, at the Selly Oak Hospital, Birmingham. The method of Brown et al (1968) was carried out at St. Bartholomew's Hospital, London. This method was adapted to a manual procedure in which cylindrical 25 ml separating funnels were used in place of the semi-automatic extractor, the 3 min.…”
Section: Methodsmentioning
confidence: 99%
“…In the original publication of ua Conaill and Muir the results obtained by the automated procedure were compared with the manual Ittrich method, as modified by Cartlidge et al (1961). Three laboratories in collaboration have now compared the automated procedure with the methods of Oakey et al (1967) andBrown et al (1968). Because the two groups had been stored differently, the results of each group were analysed separately to assess whether storage procedure had influenced the results.…”
mentioning
confidence: 99%